Thermodynamics For Physicists, Chemists and Materials Scientists - Hentschke, Reinhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Thermodynamics is the foundation of many-body physics and thus of physical chemistry and material science as well. Today new sources of useful energy, energy storage, transport and conversion, requiring development of novel technology, are of rapidly increasing importance. This development strongly affects modern industry. Thus thermodynamics will have to be given more prominence in the science curriculum in colleges and universities - something that is attempted in this book. The structure of this text is simple and transparent, enabling the easy mapping of the text onto a one-semester course syllabus and the attendant study. There are 8 chapters total and one three-part appendix. Throughout the text the student finds numerous examples (solved problems) reaching from cosmic to molecular evolution or from cloud formation to Bose condensation.
Two Fundamental Laws of Nature -- Thermodynamic Functions -- Equilibrium and Stability -- Simple Phase Diagrams -- Microscopic Interactions -- Thermodynamics and Molecular Simulation -- Non-equilibrium Thermodynamics.
Keywords: Physics; Chemistry, Physical organic; Thermodynamics; Engineering; Physics; Thermodynamics; Physical Chemistry; Statistical Physics, Dynamical Systems and Complexity; Numerical and Computational Physics; Engineering Thermodynamics, Heat and Mass Transfer